2018
DOI: 10.14349/rlp.2018.v50.n3.4
|View full text |Cite
|
Sign up to set email alerts
|

Del sexting al cibercontrol en las relaciones de pareja de adolescentes españoles: análisis de sus argumentos

Abstract: Resumen El objetivo de este estudio consiste en profundizar en el fenómeno del sexting y en sus dinámicas de ciberviolencia dentro de las relaciones de pareja de adolescentes, para ello, se van a analizar los comportamientos de sexting, las estrategias empleadas, las justificaciones y las consecuencias del sexting en función del género y el lugar de procedencia. Mediante una metodología cualitativa se realizaron 20 grupos de discusión en los que participaron 222 adolescentes, un 54% chicas y un 46% chicos, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 47 publications
1
7
0
10
Order By: Relevance
“…In this regard, Cooper, Quayle, Jonsson and Göran (2016) determine the existence of four broad topics that would cover the main ambimotivations underlying engagement in sexting: flirting with and/or attracting the partner's attention, being in a steady relationship, seeing sexting as an experimental phase of adolescence, and being put under pressure by the partner or by friends. In the Spanish context, girls' main reasons for sexting are to have or maintain an emotional relationship, whereas the boys' justifications are to achieve a sexual relationship (Alonso-Ruido, Rodríguez-Castro, Lameiras-Fernández, & Martínez-Román, 2018; Rodríguez-Castro, Alonso-Ruido, Lameiras-Fernández, & Faílde-Garrido, 2018). Moreover, several studies have focused on examining attitudes towards sexting (Samimi & Alderson, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Cooper, Quayle, Jonsson and Göran (2016) determine the existence of four broad topics that would cover the main ambimotivations underlying engagement in sexting: flirting with and/or attracting the partner's attention, being in a steady relationship, seeing sexting as an experimental phase of adolescence, and being put under pressure by the partner or by friends. In the Spanish context, girls' main reasons for sexting are to have or maintain an emotional relationship, whereas the boys' justifications are to achieve a sexual relationship (Alonso-Ruido, Rodríguez-Castro, Lameiras-Fernández, & Martínez-Román, 2018; Rodríguez-Castro, Alonso-Ruido, Lameiras-Fernández, & Faílde-Garrido, 2018). Moreover, several studies have focused on examining attitudes towards sexting (Samimi & Alderson, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The second identified profile was that of those who maintain an ambivalent view (26%), regarding people who engage in sexting as bold and flirty, while at the same time considering them to be conflictive, integrating aspects from both the positive and negative profiles. In previous qualitative studies, the results showed pretty widespread ambivalent positions among young people [46]. This ambivalence may be also a reflection of the transition and contradiction processes between the traditional sexual cultural scripts (face-to-face) and the new virtual scripts.…”
Section: Profiles On Sexting: Positive Negative and Ambivalentmentioning
confidence: 67%
“…Nuestro estudio coincide en que las mujeres han sufrido más actos violentos de carácter sexual 23 y es el grupo de mujeres el que presenta sentimientos de miedo hacia sus parejas. Si bien, al realizar la diferenciación por sexos también se observa que son las mujeres quienes tratan más con sus progenitores sus actividades en las redes, lo que se considera un factor protector 22 ,…”
Section: Discussionunclassified